Thus spoke Zarathustra : a book for all and none - Nietzsche, Friedrich Wilhelm, 1844-1900; Del Caro, Adrian, 1952-; Pippin, Robert B., 1948- (Cambridge : Cambridge University Press, 2006)
Nietzsche regarded 'Thus Spoke Zarathustra' as his most important work, and his story of the wandering Zarathustra has had enormous influence on subsequent culture. Nietzsche uses a mixture of homilies, parables, epigrams and dreams to introduce some of his most striking doctrines, including the Overman, nihilism, and the eternal return of the same. This edition offers a new translation by Adrian Del Caro which restores the original versification of Nietzsche's text and captures its poetic brilliance. Robert Pippin's introduction discusses many of the most important interpretative issues raised by the work, including who is Zarathustra and what kind of 'hero' is he and what is the philosophical significance of the work's literary form? The volume will appeal to all readers interested in one of the most original and inventive works of modern philosophy.
Thus spoke Zarathustra : a book for all and none -- Zarathustra's prologue -- The speeches of Zarathustra -- On the three metamorphoses -- On the teachers of virtue -- On the hinterworldly -- On the despisers of the body -- On the passions of pleasure and pain -- On the pale criminal -- On reading and writing -- On the tree on the mountain -- On the preachers of death -- On war and warriors -- On the new idol -- On the flies of the market place -- On chastity -- On the friend -- On a thousand and one goals -- On love for the neighbor -- On the way of the creator -- On little women old and young -- On the adder's bite -- On child and marriage -- On free death -- On the bestowing virtue -- The child with the mirror -- On the blessed isles -- On the pitying -- On priests -- On the virtuous -- On the rabble -- On the tarantulas -- On the famous wise men -- The night song -- The dance song -- The grave song -- On self-overcoming -- On the sublime ones -- On the land of education -- On immaculate perception -- On scholars -- On poets -- On great events -- The soothsayer -- On redemption -- On human prudence -- The stillest hour -- The wanderer -- On the vision and the riddle -- On unwilling bliss -- Before sunrise -- On virtue that makes small -- On the Mount of Olives -- On passing by -- On apostates -- The homecoming -- On the three evils -- On the spirit of gravity -- On old and new tablets -- The convalescent -- On great longing -- The other dance song -- The seven seals (or : the yes and amen song) -- The honey sacrifice -- The cry of distress -- Conversation with the kings -- The leech -- The magician -- Retired -- The ugliest human being -- The voluntary beggar -- The shadow -- At noon -- The welcome -- The Last Supper -- On the higher man -- The song of melancholy -- On science -- Among daughters of the desert -- The awakening -- The ass festival -- The sleepwalker song -- The sign.
Title from publisher's bibliographic system (viewed on 18 Jul 2016).
Keywords: elektronické knihy; electronic books; Superman (Philosophical concept); Philosophy